Use of an Institutional Personal Learning Environment to support learning actions in Higher Education - Pérez Cascante, Lucila; Salinas, Jesús; Marín, Victoria (AtoZ: novas práticas em informação e conhecimento, 2016)
Introduction: This paper presents a pilot experience on the use of an Institutional Personal Learning Environment (iPLE) which aimed to describe the conception, design and development of the iPLE, as well as to determine how users approached the iPLE, and to identify the structure of the Personal Learning Environments (PLEs) designed by students. Method: The iPLE supported graduated students - specialized on research for social sciences and education –of the University Casa Grande (Guayaquil, Ecuador) - in the development of their final master projects and to support other people interested in building and using a PLE. The experiment data sources included academic records, virtual classrooms design, the very PLEs built by the students, statistics of use and access to the iPLE; and a questionnaire held to the participants. Results: The initial results allow the research team to report a favorable acceptance of the iPLE by the students not only as a support for research work, but also to provide a model for the construction of PLEs. In addition, the questionnaire shows that the users of the iPLE rated the environment as having high usability and felt a high grade of satisfaction. Conclusions: The conclusions point out different lines of research related to iPLEs, such as use an iPLE as portfolio of evidence and interaction among students, peers and teachers or the customization of an iPLE by using technological and teaching learning resources.